Prognostic significance of contrast staining following mechanical thrombectomy in acute ischaemic stroke - Liping Liu; Ling Wang; Xiang Xu; Hongyi Yan; Zhonghua Yang; Jing Yan; Ximing Nie; Miao Wen; Haiyan Li; Na Wei; Dandan Yu (Stroke and Vascular Neurology)
Background Advances in endovascular thrombectomy (EVT) and extended treatment criteria have improved outcomes in acute ischaemic stroke (AIS). However, contrast staining (CS) on postoperative CT complicates clinical decision-making and outcome evaluation. We investigated the association between postoperative CS and 90-day clinical outcomes in AIS patients.Methods In this multicentre observational study, we enrolled AIS patients treated with EVT who underwent non-contrast CT (NCCT) within 2 hours postprocedure. Patients were stratified into two groups based on the presence or absence of CS to further explore the relationship between CS characteristics and clinical outcomes. The primary outcome was poor functional outcome, defined as a modified Rankin Scale score ≥3 at 90 days, evaluated with the logistic regression analysis adjusted for age, sex and other clinical features.Results Among the 420 patients (mean age 63 years; 74.3% male), CS was observed in 250 (59.5%) following EVT. Logistic regression analysis showed that CS was strongly associated with poor functional outcomes. At 3 months, the proportion of patients with functional dependence was significantly higher in the CS group (76.8%) compared with the non-CS group (62.4%). In addition, the CS group exhibited a higher death rate compared with the non-CS group (p=0.028). Our study found that CS in the pons, as well as larger and denser staining volumes, was often indicative of poor prognosis.Conclusion In around half of AIS patients with EVT, CS can be observed and independently associate with poor clinical outcomes, primarily related to the location and density of CS.